Knowledge, behaviours and anxiety of eastern part of turkey residents about the current covid-19 outbreak - Yakar, Burkay; Karakaya, Gamzecan; Pirincci, Edibe; Onalan, Erhan; Akkoc, Ramazan Fazil; Aydın, Suleyman (Mattioli 1885, 2021)
Aim: The aim of this study was to assess the knowledge and behaviors of Eastern part of Turkey residents about the COVID-19 and the relationship between the pandemic and the anxiety levels. Methods: Cross-sectional study was carried out between 07-21 April 2020 through online questionnaires. The study included 897 people who filled out the form and met the study criteria. The data was collected through a self-administered questionnaire of the socio-demographic characteristics, generalized anxiety disorder scale, opinions about the epidemic, knowledge and behaviours of individuals regarding COVID-19. Results: A total of 897 participants had a mean score of knowledge and behaviors of 5.11±1.63 and 46.81±5.65, respectively. Knowledge and behaviors score were higher in males (p<0.001) and participants with high education level (p=0.003). Anxiety level was negatively correlated with knowledge (r=-0.156, p<0.001) and behaviors scores (r=-0.288, p<0.001). There was a positive significant correlation between knowledge level and positive behav-iors score (r=0.194, p<0.001). Conclusion: Gender and education levels had a statistical effect on individuals’ COVID-19 knowledge and positive behaviors scores. COVID-19 outbreak was associated with high anxiety levels in individuals and it was determined that the anxiety caused by the epidemic negatively affected the knowledge and positive bahaviours of the individuals. © Mattioli 1885.
Keywords: Anxiety; Behaviours; COVID-19; Knowledge; Novel coronavirus; SARS-CoV-2